The Pancreatic Islet Beta Cell-Enriched Transcription Factor Pdx-1 Regulates Slc30a8 Gene Transcription Through an Intronic Enhancer - Pound, Lynley D. (2011)
The SLC30A8 gene encodes the zinc transporter ZnT-8, which provides zinc for insulin-hexamer formation. Genome-wide association studies have shown that a polymorphic variant in SLC30A8 is associated with altered susceptibility to type 2 diabetes and we recently reported that glucose-stimulated insulin secretion is decreased in islets isolated from Slc30a8 knockout mice. The present study examines the molecular basis for the islet-specific expression of Slc30a8. VISTA analyses identified two conserved regions in Slc30a8 introns 2 and 3, designated enhancers A and B, respectively. Transfection experiments demonstrated that enhancer B confers elevated fusion gene expression in both βTC-3 cells and αTC-6 cells. In contrast, enhancer A confers elevated fusion gene expression selectively in βTC-3 and not αTC-6 cells. These data suggest that enhancer A is an islet beta cell-specific enhancer and that the mechanisms controlling Slc30a8 expression in alpha and beta cells are overlapping but distinct. Gel retardation and chromatin immunoprecipitation (ChIP) assays revealed that the islet-enriched transcription factor Pdx-1 binds enhancer A in vitro and in situ, respectively. Mutation of two Pdx-1 binding sites in enhancer A markedly reduces fusion gene expression suggesting that this factor contributes to Slc30a8 expression in beta cells, a conclusion consistent with developmental studies showing that restriction of Pdx-1 to pancreatic islet beta cells correlates with the induction of Slc30a8 gene and ZnT-8 protein expression in vivo.